Production of Industrial Reclaimed Water: A Case Study of Aquapolo in the Municipality of São Paulo - SP - Mulla, Thais Santin; Achon, Cali Laguna (Technical and Scientific Journal Green Cities, 2025)
Water resources are essential, and their scarcity, often caused by the discrepancy between water availability and population density, creates significant societal impacts. This study addresses the Aquapolo wastewater treatment plant, located in the city of São Paulo, which emerges as an alternative to mitigate the problem in this region. The article aims to provide an analysis of industrial reclaimed water production, for non-potable purposes, through a case study methodology, exploring aspects such as the plant's installed and utilized capacity, diversification of companies receiving reclaimed water, installed treatment units, generated waste, as well as treated effluent quality data. Finally, the use of a SWOT matrix revealed negative points, such as the underutilization of installed capacity and the 90% dependence on a single consumer, in addition to positive aspects, such as water quality with turbidity below 1 NTU, reduced effluent discharge into water bodies, and a high treated flow rate, highlighting the strengths and opportunities of the project.
Keywords: Wastewater treatment; Aquapolo; Sustainability